Positive electrode active material for lithium ion battery, positive electrode active material for sodium ion battery, positive electrode material, solid-state battery, and method of producing positive electrode active material for lithium ion battery

KR103013090B1Active Publication Date: 2026-09-01TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020230174529
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-05
Publication Date
2026-09-01
Estimated Expiration
2043-12-05

Smart Images

  • Figure 112023136210798-PAT00002_ABST
    Figure 112023136210798-PAT00002_ABST
Patent Text Reader

Abstract

In the X-ray diffraction measurement results, there are three or more peaks in the range of 2θ from 64° to 70°, and one peak in the range of 2θ from 15° to 20°, and Positive electrode active material for lithium-ion batteries belonging to the space group Cmca.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a positive electrode active material for a lithium-ion battery, a positive electrode active material for a sodium-ion battery, a positive electrode material, a solid-state battery, and a method for manufacturing a positive electrode active material for a lithium-ion battery. Background Technology

[0002] A positive electrode active material having at least one structure selected from O2 type structure, T#2 type structure and O6 type structure is stable up to high potential, so it has a large discharge capacity in the high potential range.

[0003] Patent Document 1 describes a "positive electrode active material used in a non-aqueous electrolyte secondary battery comprising a lithium-containing transition metal oxide having a layered structure, wherein the main arrangement of the transition metal, oxygen, and lithium appears as an O2 structure, and wherein the lithium-containing transition metal oxide has Li, Mn, and element M in the lithium-containing transition metal layer of the layered structure, and has a general compositional formula Li x [Li α (Mn a M b ) 1-α A “positive electrode active material for a non-aqueous electrolyte secondary battery” has been proposed, represented as ]O2, wherein 0.5 < x < 1.1, 0.1 < α < 0.33, 0.67 < a < 0.97, 0.03 < b < 0.33, and M is at least one element selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi.

[0004] Also, in Patent Document 2, "space group P6 3 Lithium-containing layered oxide belonging to mc a Na b M c O 2±αA positive electrode active material for a non-aqueous electrolyte secondary battery is proposed, characterized in that the potential P (V) of (0.5 ≤ a ≤ 1.3, 0 ≤ b ≤ 0.01, 0.90 ≤ c ≤ 1.10, 0 ≤ α ≤ 0.3, M = at least one element selected from manganese, cobalt, nickel, iron, aluminum, molybdenum, zirconium, and magnesium) is in the range of 4.8 ≤ P ≤ 5.0 (vs. Li / Li+), the molar ratio of lithium to M is set to a and c, respectively, and the ratio of a when c is converted to 1.0 is in the range of 0.08 ≤ a ≤ 0.12. Prior art literature

[0005] Japanese Published Patent Application No. 2014-186937 Japanese Published Patent Application No. 2010-92824 The problem to be solved

[0006] A positive electrode active material having at least one structure selected from O2 type, T#2 type, and O6 type structures undergoes a structural change between the O2 type, T#2 type, and O6 type structures during charging and discharging. Specifically, the structure changes in the order of O2 type, T#2 type, O6 type, and O2 type, extending from the side with a high Li content to the side with a low Li content. Since the volume of the positive electrode active material expands and contracts significantly in accordance with this structural change, cracks may occur in the positive electrode active material. If this happens, the electron conduction path becomes fragmented, making it prone to a decrease in the capacity retention rate after repeated charging and discharging.

[0007] Therefore, the problem that one embodiment of the present disclosure aims to solve is to provide a positive electrode active material for a lithium-ion battery that has a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0008] The problem that another embodiment of the present disclosure aims to solve is to provide a positive electrode active material for a sodium ion battery that has a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0009] The problem that another embodiment of the present disclosure aims to solve is to provide a positive electrode material that enables a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0010] The problem that another embodiment of the present disclosure aims to solve is to provide a solid-state battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0011] The problem that another embodiment of the present disclosure aims to solve is to provide a method for manufacturing a positive electrode active material that obtains a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging. means of solving the problem

[0012] The means for solving the above problem include the following means.

[0013] <1> In the X-ray diffraction measurement results, there are three or more peaks in the range of 2θ from 64° to 70°, and one peak in the range of 2θ from 15° to 20°, and

[0014] Positive electrode active material for lithium-ion batteries belonging to the space group Cmca.

[0015] <2> A positive electrode active material for a lithium-ion battery described in <1>, which is a compound represented by the following formula 1.

[0016] Equation 1: Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2

[0017] (In the above Equation 1, a, b, x, y, z, p, q, and r are numbers satisfying 0 ≤ a ≤ 1, 0 ≤ b ≤ 0.05, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0018] M represents at least one type selected from the group consisting of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.

[0019] <3> A positive electrode active material for a sodium ion battery, which is a compound represented by Formula 2 below.

[0020] Equation 2: Na c Mn x-p Ni y-q Co z-r M p+q+r O2

[0021] (In the above Equation 2, c, x, y, z, p, q, and r are numbers satisfying 0.5 ≤ c ≤ 0.65, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0022] M represents at least one type selected from the group consisting of Li, B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.

[0023] <4> A positive electrode material comprising a positive electrode active material for a lithium-ion battery as described in <1> or <2>.

[0024] A solid-state battery comprising a positive electrode active material for a lithium-ion battery as described in <5> <1> or <2>.

[0025] <6> A method for manufacturing a positive electrode active material for a lithium-ion battery having a process of ion-exchanging Na contained in a compound represented by Formula 2 below with Li.

[0026] Equation 2: Na c Mn x-p Ni y-q Co z-r M p+q+r O2

[0027] (In the above Equation 2, c, x, y, z, p, q, and r are numbers satisfying 0.5 ≤ c ≤ 0.65, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0028] M represents at least one type selected from the group consisting of Li, B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W. Effects of the invention

[0029] According to one embodiment of the present disclosure, a positive electrode active material for a lithium-ion battery is provided, which obtains a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0030] According to another embodiment of the present disclosure, a positive electrode active material for a sodium ion battery is provided, which obtains a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0031] According to another embodiment of the present disclosure, a positive electrode material is provided that enables a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0032] According to another embodiment of the present disclosure, a solid-state battery is provided having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging.

[0033] According to another embodiment of the present disclosure, a method for manufacturing a positive electrode active material is provided, which obtains a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging. Brief explanation of the drawing

[0034] Figure 1 is a schematic cross-sectional view showing an example of a solid-state battery. Specific details for implementing the invention

[0035] Hereinafter, an embodiment that is an example of the present disclosure will be described. The description and examples provided are intended to illustrate embodiments and do not limit the scope of the invention.

[0036] In numerical ranges described stepwise in this specification, an upper or lower limit value described in one numerical range may be substituted with an upper or lower limit value of another numerical range described stepwise. Additionally, in numerical ranges described in this specification, an upper or lower limit value of said numerical range may be substituted with a value shown in the examples.

[0037] Each component may contain multiple types of the corresponding substance.

[0038] When referring to the amount of each component in a composition, if there are multiple types of substances corresponding to each component in the composition, unless specifically mentioned otherwise, it means the total amount of said multiple types of substances present in the composition.

[0039] The term “process” includes not only independent processes but also cases where a process cannot be clearly distinguished from other processes, provided that its intended function is achieved.

[0040] <Positive electrode active material for lithium-ion batteries>

[0041] The positive electrode active material for a lithium-ion battery related to the present disclosure has, in the X-ray diffraction measurement results, three or more peaks in the range of 2θ from 64° to 70° and one peak in the range of 2θ from 15° to 20°, and is attributed to the space group Cmca.

[0042] The positive electrode active material for a lithium-ion battery related to the present disclosure is a positive electrode active material for a lithium-ion battery that, by the above composition, obtains a battery having a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging. The reason for this is presumed to be as follows.

[0043] The positive electrode active material for a lithium-ion battery related to the present disclosure has, in the X-ray diffraction measurement results, three or more peaks in the range of 2θ from 64° to 70° and one peak in the range of 2θ from 15° to 20°, and belongs to the space group Cmca. By adopting this configuration, the structure of the positive electrode active material for a lithium-ion battery becomes close to a single phase of the T#2 type structure. By doing so, changes in the structure between the O2 type structure and the T#2 type structure can be suppressed. Consequently, the expansion and contraction of the volume of the positive electrode active material for a lithium-ion battery accompanying structural changes can be suppressed. As a result, cracks are less likely to occur in the positive electrode active material, and the decrease in capacity retention rate after repeated charging and discharging is suppressed. Furthermore, as the structure of the positive electrode active material for a lithium-ion battery becomes close to a single phase of the T#2 type structure, the discharge capacity increases.

[0044] Hereinafter, a positive electrode active material for a lithium-ion battery related to the present disclosure will be described.

[0045] (Peak location in X-ray diffraction measurement results)

[0046] The positive electrode active material for a lithium-ion battery related to the present disclosure has, in the X-ray diffraction measurement results, three or more peaks in the range of 2θ from 64° to 70° and one peak in the range of 2θ from 15° to 20°.

[0047] In order to obtain a positive electrode active material for a lithium-ion battery of the said composition, it is preferable to manufacture it by the method for manufacturing a positive electrode active material for a lithium-ion battery related to the present disclosure.

[0048] The number of peaks existing in the range of 2θ between 64° and 70° and the number of peaks existing in the range of 15° to 20° are measured by X-ray diffraction. The RINT-2000 manufactured by Rigaku Co., Ltd. can be used as the X-ray diffraction measuring device. The measurement procedure is described below.

[0049] X-ray diffraction measurements are performed under conditions of 0.01° step and 0.1 s / step or longer, such that 2θ covers a range of at least 10° to 70°. S = R WP / R e Fitting is performed using the Rietveld method so that θ is 1.3 or less, and the number of separated peaks is counted as the number of peaks. Fitting is performed for the entire measurement range including the range of 2θ from 10° to 70°. Among the fitting results, the number of peaks existing in the range of 2θ from 64° to 70° and the number of peaks existing in the range of 2θ from 15° to 20° are determined.

[0050] (Space group)

[0051] The positive electrode active material for a lithium-ion battery related to the present disclosure belongs to the space group Cmca.

[0052] Here, whether it belongs to the space group Cmca is determined from the fitting results by the Rietveld method described above. Among the phases included in the fitting results by the Rietveld method, if the phase belonging to the space group Cmca exists in a volume ratio of 90% or more, it is determined that the positive electrode active material belongs to the space group Cmca.

[0053] For a positive electrode active material for a lithium-ion battery, it is preferable that the phase belonging to the space group Cmca is 95% or more by volume, and more preferable that it is 98% or more.

[0054] (Composition formula of positive electrode active material for lithium-ion batteries)

[0055] In terms of initial discharge capacity and capacity retention rate, the positive electrode active material for a lithium-ion battery related to the present disclosure is preferably a compound represented by the following formula 1.

[0056] Equation 1: Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2

[0057] In the above Equation 1, a, b, x, y, z, p, q, and r are numbers satisfying 0 ≤ a ≤ 1, 0 ≤ b ≤ 0.05, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0058] M represents at least one type selected from the group consisting of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.

[0059] It is preferable that x is a number satisfying 0 ≤ x ≤ 1, and more preferable that x is a number satisfying 0.1 ≤ x ≤ 1.

[0060] It is preferable that y be a number satisfying 0 ≤ y ≤ 0.5, and more preferable that y be a number satisfying 0 ≤ y ≤ 0.33.

[0061] It is preferable that z is a number satisfying 0 ≤ z ≤ 1, and more preferable that z is a number satisfying 0 ≤ z ≤ 0.67.

[0062] It is desirable that p is a number satisfying 0 ≤ p ≤ 0.10.

[0063] It is desirable that q be a number satisfying 0 ≤ q ≤ 0.10.

[0064] It is desirable that r is a number satisfying 0 ≤ r ≤ 0.10.

[0065] The positive electrode active material related to the present disclosure is, specifically, Li 0.60 Na 0.00Mn 0.50 Ni 0.20 Co 0.30 O2, Li 0.50 Na 0.00 Mn 0.50 Ni 0.20 Co 0.30 O2, Li 0.60 Na 0.05 Mn 0.50 Ni 0.20 Co 0.30 O2, Li 0.60 Na 0.00 Mn 0.67 Ni 0.33 O2, Li 0.60 Na 0.00 Mn 0.40 Ni 0.20 Co 0.30 Cr 0.10 O2, Li 0.60 Na 0.00 Mn 0.50 Ni 0.10 Co 0.30 Mg 0.10 O2, etc. can be cited.

[0066] <Method for manufacturing positive electrode active material for lithium-ion batteries>

[0067] A method for manufacturing a positive electrode active material for a lithium-ion battery related to the present disclosure has a process (ion exchange process) of ion-exchanging Na contained in a compound represented by Formula 2 below with Li.

[0068] Equation 2: Na c Mn x-p Ni y-q Co z-r M p+q+r O2

[0069] In the above Equation 2, c, x, y, z, p, q, and r are numbers satisfying 0.5 ≤ c ≤ 0.65, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0070] M represents at least one type selected from the group consisting of Li, B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.

[0071] It is preferable that x is a number satisfying 0 ≤ x ≤ 1, and more preferable that x is a number satisfying 0.1 ≤ x ≤ 1.

[0072] It is preferable that y be a number satisfying 0 ≤ y ≤ 0.5, and more preferable that y be a number satisfying 0 ≤ y ≤ 0.33.

[0073] It is preferable that z is a number satisfying 0 ≤ z ≤ 1, and more preferable that z is a number satisfying 0 ≤ z ≤ 0.67.

[0074] It is desirable that p is a number satisfying 0 ≤ p ≤ 0.10.

[0075] It is desirable that q be a number satisfying 0 ≤ q ≤ 0.10.

[0076] It is desirable that r is a number satisfying 0 ≤ r ≤ 0.10.

[0077] (Na-doped precursor synthesis process)

[0078] The method for manufacturing a positive electrode active material for a lithium-ion battery related to the present disclosure may, if necessary, include a process for synthesizing a compound represented by Formula 2 (hereinafter also referred to as a Na-doped precursor).

[0079] The Na-doped precursor is synthesized by a known method.

[0080] As for Na-doped precursors, specifically, Na 0.60 Mn 0.5 Ni 0.2 Co 0.3 O2, Na 0.50 Mn 0.50 Ni 0.20 Co 0.30 O2, Na 0.60 Mn 0.67 Ni 0.33 O2, Na 0.60 Mn 0.40 Ni 0.20 Co 0.30 Cr 0.10 O2, Na 0.60Mn 0.50 Ni 0.10 Co 0.30 Mg 0.10 Examples include O2.

[0081] (Ion exchange process)

[0082] The ion exchange process is a process of ion-exchanging Na contained in the Na-doped precursor with Li.

[0083] Ion exchange of the Na dope precursor can utilize a molten salt phase mixed with lithium nitrate and lithium chloride.

[0084] It is preferable that the temperature conditions during ion exchange be in the range of above the melting temperature of the molten salt phase and below 320°C.

[0085] <Positive electrode active material for sodium ion batteries>

[0086] The compound represented by Formula 2 below can be effectively used as a positive electrode active material for sodium ion batteries.

[0087] Equation 2: Na c Mn x-p Ni y-q Co z-r M p+q+r O2

[0088] In the above Equation 2, c, x, y, z, p, q, and r are numbers satisfying 0.5 ≤ c ≤ 0.65, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and

[0089] M represents at least one type selected from the group consisting of Li, B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.

[0090] A specific example of a positive electrode active material for a sodium ion battery related to the present disclosure is Na 0.60 Mn 0.5 Ni 0.2 Co 0.3 O2, Na 0.50 Mn 0.50 Ni 0.20 Co 0.30 O2, Na0.60 Mn 0.67 Ni 0.33 O2, Na 0.60 Mn 0.40 Ni 0.20 Co 0.30 Cr 0.10 O2, Na 0.60 Mn 0.50 Ni 0.10 Co 0.30 Mg 0.10 Examples include O2.

[0091] The positive electrode active material for a sodium ion battery related to the present disclosure can be used as a Na-doped precursor for the method of manufacturing a positive electrode active material for a lithium ion battery related to the present disclosure.

[0092] <Materials for Straight Drama>

[0093] The positive electrode material related to the present disclosure contains a positive electrode active material for a lithium-ion battery and, if necessary, may contain a conductivity aid, a solid electrolyte, a binder, and other components.

[0094] (Positive electrode active material for lithium-ion batteries)

[0095] The positive electrode active material for a lithium-ion battery included in the positive electrode material related to the present disclosure is the same as the positive electrode active material for a lithium-ion battery related to the present disclosure, and the preferred embodiment is also the same.

[0096] The positive electrode active material for a lithium-ion battery included in the positive electrode material related to the present disclosure may contain a positive electrode active material for a lithium-ion battery other than the positive electrode active material for a lithium-ion battery related to the present disclosure.

[0097] As a positive electrode active material for other lithium-ion batteries, it is preferable to include a lithium composite oxide. The lithium composite oxide may contain at least one selected from the group consisting of F, Cl, N, S, Br, and I. In addition, the lithium composite oxide may have a crystal structure belonging to at least one space group selected from space groups R-3m, Immm, and P63-mmc (also referred to as P63mc or P6 / mmc). In addition, the lithium composite oxide may have an O2 type structure in which the main arrangement of transition metals, oxygen, and lithium is O2.

[0098] Lithium composite oxides having a crystal structure belonging to R-3m include, for example, Li x Me y O α X β Examples of compounds represented by (Me represents at least one selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and X represents at least one selected from the group consisting of F, Cl, N, S, Br, and I, satisfying 0.5 ≤ x ≤ 1.5, 0.5 ≤ y ≤ 1.0, 1 ≤ α < 2, and 0 < β ≤ 1).

[0099] As lithium composite oxides having a crystal structure belonging to Immm, for example, Li x1 M 1 A 1 2 (satisfying 1.5 ≤ x1 ≤ 2.3), and M 1 It comprises at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe, and A 1 ... contains at least oxygen, and A 1 Complex oxides represented as (specific example Li2NiO2), Li (where the proportion of oxygen occupied in is 85 atomic% or more), Li x1 M1A 1-x2 M 1B x2 O 2-y A 2 y (0 ≤ x2 ≤ 0.5, 0 ≤ y ≤ 0.3, and at least one of x2 and y is not 0, and M 1A represents at least one type selected from the group consisting of Ni, Co, Mn, Cu, and Fe, and M 1B represents at least one type selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta, and W, and A 2 Examples of complex oxides represented by ) represent at least one type selected from the group consisting of F, Cl, Br, S, and P.

[0100] Lithium composite oxides having a crystal structure belonging to P63-mmc include, for example, M1 x M2 y Examples of complex oxides include O2 (where M1 represents an alkali metal (at least one of Na and K is preferred), M2 represents a transition metal (at least one selected from the group consisting of Mn, Ni, Co and Fe is preferred), and x + y satisfies 0 < x + y ≤ 2).

[0101] As lithium composite oxides having an O2 type structure, for example, Li x [Li α (Mn a Co b M c ) 1-αExamples include complex oxides represented by ]O2 (0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, where M represents at least one selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W, and Bi), and as a specific example, Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2, etc. can be cited.

[0102] It is more preferable that at least a portion of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As for the halide solid electrolyte coating at least a portion of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6(0 < x < 1, 0 < b ≤ 1.5) [LTAF electrolyte] is preferred.

[0103] (Challenge Supplement)

[0104] Examples of conductivity aids include carbon materials, metal materials, and conductive polymer materials. Examples of carbon materials include carbon black (e.g., acetylene black, furnace black, Ketjen black, etc.), fibrous carbon (e.g., vapor-phase carbon fiber, carbon nanotube, carbon nanofiber, etc.), graphite, fluorocarbon, etc. Examples of metal materials include metal powder (e.g., aluminum powder, etc.), conductive whiskers (e.g., zinc oxide, potassium titanate, etc.), and conductive metal oxides (e.g., titanium oxide, etc.). Examples of conductive polymer materials include polyaniline, polypyrrole, polythiophene, etc. One type of conductivity aid may be used alone, or two or more types may be used in combination.

[0105] (Solid electrolyte)

[0106] As a solid electrolyte, it is preferable to include at least one solid electrolyte species selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halogen solid electrolytes.

[0107] As a sulfide solid electrolyte, it is preferable to contain sulfur (S) as the main component of an anionic element, and furthermore, to contain, for example, an element Li and an element A. The element A is at least one selected from the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may additionally contain O and at least one of a halogen element. Examples of halogen elements (X) include F, Cl, Br, I, etc. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100-x)P2S5(70 ≤ x ≤ 80) and yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7 ≤ x ≤ 0.8, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30). The sulfide solid electrolyte may have a composition represented by the following general formula (1).

[0108] Li 4-x Ge 1-x P x S4(0 < x < 1) … Equation (1)

[0109] In Equation (1), at least a portion of Ge may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Also, at least a portion of P may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A portion of Li may be substituted with at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A portion of S may be substituted with a halogen. As for the halogen, it is at least one of F, Cl, Br, and I.

[0110] The oxide solid electrolyte contains oxygen (O) as the main component of an anionic element and may also contain Li and Q elements (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S). Examples of oxide solid electrolytes include garnet-type solid electrolytes, perovskite-type solid electrolytes, nasicon-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. Examples of garnet-type solid electrolytes include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0 ≤ x ≤ 2), Li5La3Nb2O 12Examples include perovskite-type solid electrolytes such as (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. Examples of nasicon-type solid electrolytes such as Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. Examples of Li-PO-based solid electrolytes such as Li3PO4 and LIPON (a compound in which some of the O of Li3PO4 are replaced with N), and examples of Li-BO-based solid electrolytes such as Li3BO3 and a compound in which some of the O of Li3BO3 are replaced with C, etc.

[0111] As a halide solid electrolyte, a solid electrolyte comprising Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is preferred. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6(0 < x < 1, 0 < b ≤ 1.5) is preferable. Li 6-3z Y z Among X6, Li3YX6 (where X represents Cl or Br) is more preferable due to its excellent lithium ion conductivity, and furthermore, Li3YCl6 is preferred. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6(0 < x < 1, 0 < b ≤ 1.5) is preferably included together with a solid electrolyte, such as a sulfide solid electrolyte, for example, from the perspective of suppressing the oxidative decomposition of the sulfide solid electrolyte.

[0112] (bookbinder)

[0113] Examples of binders include vinyl halogenated resins, rubbers, and polyolefin resins. Examples of vinyl halogenated resins include polyvinylidene fluoride (PVdF) and copolymers of polyvinylidene fluoride and hexafluoropropylene (PVdF-HFP). Examples of polyolefin resins include butadiene rubber (BR), acrylate butadiene rubber (ABR), styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), and butyl rubber (isobutylene-isoprene rubber). Examples of polyolefin resins include polyethylene and polypropylene. The binder may be a diene-based rubber containing double bonds in the main chain, for example, a butadiene-based rubber in which butadiene accounts for 30 mol% or more of the total.

[0114] (Other ingredients)

[0115] Other components may include, for example, oxide solid electrolytes, halogen solid electrolytes, thickeners, surfactants, dispersants, wetting agents, defoaming agents, solvents, etc.

[0116] <Solid-state Battery>

[0117] A solid-state battery related to the present disclosure includes a positive electrode active material for a lithium-ion battery related to the present disclosure.

[0118] A solid-state battery related to the present disclosure preferably comprises a positive electrode layer, a negative electrode layer, and an electrolyte layer or separator disposed between the positive electrode layer and the negative electrode layer. Furthermore, the positive electrode layer preferably comprises the positive electrode material of the present disclosure.

[0119] (Battery structure)

[0120] Solid-state batteries include so-called all-solid-state batteries that use an inorganic solid electrolyte as the electrolyte (where the content of the electrolyte as the electrolyte is less than 10 mass% relative to the total amount of electrolyte).

[0121] The structure of the solid-state battery of the present disclosure may be a structure comprising a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, and, for example, may be a structure shown in FIG. 1. The solid electrolyte layer (B) in FIG. 1 may be a two-layer structure. FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery. The solid-state battery shown in FIG. 1 comprises a negative electrode including a negative electrode current collector (113) and a negative electrode layer (A), a solid electrolyte layer (B), and a positive electrode including a positive electrode current collector (115) and a positive electrode layer (C). The negative electrode layer (A) comprises a negative electrode active material (101), a conductive aid (105), a binder (109), and a solid electrolyte (102). The positive electrode layer (C) includes a positive electrode active material (103), a binder (111), and a solid electrolyte (102).

[0122] When a set of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer is used as a power generation unit, the solid-state battery may have only one power generation unit or two or more. When the solid-state battery has two or more power generation units, the power generation units may be connected in series or in parallel.

[0123] The solid-state battery may be configured by encapsulating a cross-section (side) of a stacked structure of a positive electrode layer / solid electrolyte layer / negative electrode layer with resin. The current collector of the electrode may be configured such that a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer is disposed on its surface.

[0124] The shape of the solid-state battery is not particularly limited and may be, for example, coin type, cylindrical type, prismatic type, sheet type, button type, flat type, or stacked type.

[0125] (Electrolyte layer and separator)

[0126] A solid-state battery is equipped with an electrolyte layer or a separator.

[0127] The electrolyte layer may be a layer containing a solid electrolyte.

[0128] In the case of a layer containing a solid electrolyte (solid electrolyte layer), it is preferable that the solid electrolyte layer comprises one selected from the group consisting of sulfide solid electrolytes, oxide solid electrolytes, and halogen solid electrolytes.

[0129] Specific examples of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes are the same as those already described.

[0130] The solid electrolyte layer may be a single-layer structure or a multi-layer structure of two or more layers.

[0131] The solid electrolyte layer may or may not include a binder. The binder that may be included in the solid electrolyte layer is the same as that of the binder already described.

[0132] As a separator, a porous sheet (film) made of resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide can be used.

[0133] (Polar layer)

[0134] A solid-state battery comprises a positive electrode layer. The positive electrode layer comprises the positive electrode material of the present disclosure.

[0135] (The entire drama house)

[0136] A solid-state battery may additionally be provided with a positive electrode current collector. The positive electrode current collector collects current from the positive electrode layer. The positive electrode current collector is positioned on the opposite side from the electrolyte layer (or separator) with respect to the positive electrode layer.

[0137] The positive electrode current collector may be, for example, stainless steel, aluminum, copper, nickel, iron, titanium, carbon, etc., and aluminum alloy foil or aluminum foil is preferred. The aluminum alloy foil and aluminum foil may be manufactured using powder. The shape of the positive electrode current collector is, for example, thin or mesh.

[0138] The positive electrode current collector may be configured with a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on its surface.

[0139] (Polar layer)

[0140] A solid-state battery comprises a negative electrode layer. The negative electrode layer contains a negative electrode active material. If necessary, the negative electrode layer may contain at least one of a solid electrolyte for the negative electrode, a conductivity aid, and a binder. Examples of negative electrode active materials include Li-based active materials such as metallic lithium, carbon-based active materials such as graphite, oxide-based active materials such as lithium titanate, and Si-based active materials such as Si element. The conductivity aid, the solid electrolyte for the negative electrode, and the binder used in the negative electrode layer may be the same as those exemplified as the conductivity aid included in the positive electrode layer, the solid electrolyte included in the solid electrolyte layer, and the binder.

[0141] (The entire Bu-geuk house)

[0142] The solid-state battery may additionally be provided with a negative electrode current collector. The negative electrode current collector collects current from the negative electrode layer. The negative electrode current collector is positioned on the opposite side from the electrolyte layer (or separator) with respect to the negative electrode layer.

[0143] Examples of negative electrode current collectors include stainless steel, aluminum, copper, nickel, iron, titanium, carbon, etc., and copper is preferred. The shape of the negative electrode current collector is, for example, thin or mesh.

[0144] The negative electrode current collector may be configured with a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on its surface.

[0145] <Method for manufacturing a solid-state battery>

[0146] A method for manufacturing a solid-state battery related to the present disclosure is,

[0147] A process for preparing a positive electrode layer, a negative electrode layer, an electrolyte layer, or a separator (preparation process) and,

[0148] There is a process (stacking process) of stacking a positive electrode layer, an electrolyte layer or a separator, and a negative electrode layer in this order.

[0149] (Preparation process)

[0150] The preparation process is a process of preparing the positive electrode layer, the negative electrode layer, and the electrolyte layer or separator.

[0151] The method of manufacturing the positive electrode layer, the negative electrode layer, and the electrolyte layer is not particularly limited, and it is preferable to manufacture them by mixing components that may be contained in the positive electrode layer, the negative electrode layer, and the electrolyte layer to obtain a slurry, applying the slurry to a substrate, and pressing the dried film obtained by drying.

[0152] The method of mixing the components that may be contained in the positive electrode layer when obtaining the slurry is not particularly limited, and methods such as mixing using a mixing device may be used. Examples of mixing devices include ultrasonic homogenizers, shakers, thin film rotary mixers, dissolvers, homomixers, kneaders, roll mills, sand mills, atters, ball mills, vibrator mills, and high-speed impeller mills.

[0153] Methods for pressing dry films include roll presses and cold isostatic pressing (CIP).

[0154] The pressure during pressing is preferably 0.1 t / cm² or more, more preferably 0.5 t / cm² or more, and even more preferably 1 t / cm² or more. The pressure during pressing is preferably 10 t / cm² or less, more preferably 8 t / cm² or less, and even more preferably 6 t / cm² or less.

[0155] Commercially available porous sheets (films) can be used as separators.

[0156] (Lamination process)

[0157] The stacking process is a process of stacking a positive electrode layer, an electrolyte layer or separator, and a negative electrode layer in this order.

[0158] In the lamination process, it is preferable to obtain a laminate (electrode body) by laminating the positive electrode layer prepared in the preparation process, the electrolyte layer or separator, and the negative electrode layer in this order, and pressing as needed.

[0159] It is preferable to manufacture a solid-state battery related to the present disclosure through the above process.

[0160] Examples

[0161] Examples are described below, but the present invention is not limited to these examples in any way. Furthermore, in the following description, unless specifically stated otherwise, "parts" and "%" are all based on mass.

[0162] <Example 1>

[0163] [Manufacture of positive electrode active material for lithium-ion batteries]

[0164] (Na-doped precursor synthesis process)

[0165] Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, and Co(NO3)2·6H2O were used as raw materials and dissolved in pure water such that the molar ratio of Mn, Ni, and Co was 5:2:3. A Na2CO3 solution with a concentration of 12 mass% was prepared, and these two solutions were added simultaneously into a beaker. At this time, the addition rate was controlled so that the pH was 7.0 or higher and less than 7.1. After the addition was finished, the mixed solution was stirred for 24 hours under conditions of 50°C and 300 rpm. The obtained reaction product was washed with pure water, and only the precipitated powder was separated by centrifugation. The obtained powder was dried under conditions of 120°C and 48 hours, and then crushed in an agate mortar to obtain a powder (hereinafter, the powder is referred to as "intermediate powder").

[0166] To the obtained intermediate powder, Na2CO3 was added, with a composition ratio of Na2CO3. 0.60 Mn 0.5 Ni 0.2 Co 0.3 O2 was added and mixed. The mixed powder was pressed under a load of 2 ton using a cold isostatic pressing method to produce pellets. The obtained pellets were pre-calcined in air at 600 ℃ for 6 hours and calcined at 700 ℃ for 24 hours, then cooled to 250 ℃ at a rate of 3 ℃ / min and air-cooled to produce a Na-doped precursor (Na 0.60 Mn 0.5 Ni 0.2 Co 0.3 O2) was synthesized.

[0167] (Ion exchange process)

[0168] A mixed powder was obtained by mixing LiNO3 and LiCl in a mass ratio of 88:12. The mixture was weighed so that the ratio of the molar amount of Li contained in the mixed powder to the molar amount of the Na-doped precursor was 10 times. The Na-doped precursor and the mixed powder were mixed, and ion exchange was performed in air at 280 °C for 1 hour. After ion exchange, water was added to dissolve the salt, and additional washing was performed to obtain a positive electrode active material 1 for a lithium-ion battery having an O2-type structure (Li 0.58 Mn 0.50 Ni 0.20 Co 0.30 Obtained O2.

[0169] [Manufacturing of Solid-State Batteries]

[0170] (Preparation process)

[0171] -Preparation of the Acting Layer-

[0172] 85 g of positive electrode active material 1 for lithium-ion batteries (made into a powder by ball milling) and 10 g of carbon black, a conductivity aid, were introduced into 125 mL of a solvent n-methylpyrrolidone solution in which 5 g of polyvinylidene fluoride (PVDF), a binder, was dissolved, and a slurry was prepared by kneading until uniformly mixed. This slurry was applied to a single surface of an Al positive electrode current collector with a thickness of 15 μm at a weight of 6 mg / cm² per unit area, and an electrode was obtained by drying. Subsequently, this electrode was pressed to achieve a positive electrode layer thickness of 45 μm and a positive electrode layer density of 2.4 g / cm³. Finally, this electrode was cut to a diameter of 16 mm to obtain a positive electrode having a positive electrode layer and a positive electrode current collector.

[0173] -Preparation of the negative polarity layer-

[0174] A Li foil was cut to a diameter of 19 mm to obtain a negative electrode layer.

[0175] -Preparation of Separator-

[0176] A porous PP sheet was prepared as a separator.

[0177] (Lamination process)

[0178] A laminate was obtained by stacking a positive electrode, a separator, and a negative electrode layer in this order. Additionally, the positive electrode was stacked such that the positive electrode layer faced the separator. A CR2032 type coin cell battery was fabricated by placing the laminate and a non-aqueous electrolyte (a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 3:7, with lithium hexafluorophosphate (LiPF6) dissolved as a support salt at a concentration of 1 mol / L) into a coin cell.

[0179] <Example 2>

[0180] [Manufacture of positive electrode active material for lithium-ion batteries]

[0181] In the (Na-doped precursor synthesis process), regarding the intermediate powder, Na2CO3, Na 0.50 Mn 0.5 Ni 0.2 Co 0.3 A positive electrode active material for a lithium-ion battery was obtained in the same order as in Example 1, except that O2 was added. The positive electrode active material for a lithium-ion battery is a positive electrode active material for a lithium-ion battery 2 (Li 0.52 Mn 0.50 Ni 0.20 Co 0.30 O2) is used.

[0182] [Manufacturing of Solid-State Batteries]

[0183] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material 2 for a lithium-ion battery.

[0184] <Comparative Example 1>

[0185] [Manufacture of positive electrode active material for lithium-ion batteries]

[0186] In the (Na-doped precursor synthesis process), regarding the intermediate powder, Na2CO3, Na 0.70 Mn0.5 Ni 0.2 Co 0.3 A positive electrode active material for a lithium-ion battery was obtained in the same order as in Example 1, except that O2 was added. The positive electrode active material for a lithium-ion battery is lithium-ion battery positive electrode active material C1 (Li 0.67 Mn 0.50 Ni 0.20 Co 0.30 O2) is used.

[0187] [Manufacturing of Solid-State Batteries]

[0188] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material C1 for a lithium-ion battery.

[0189] <Comparative Example 2>

[0190] [Manufacture of positive electrode active material for lithium-ion batteries]

[0191] In the (Na-doped precursor synthesis process), regarding the intermediate powder, Na2CO3, Na 0.40 Mn 0.5 Ni 0.2 Co 0.3 A positive electrode active material for a lithium-ion battery was obtained in the same order as in Example 1, except that O2 was added. The positive electrode active material for a lithium-ion battery is lithium-ion battery positive electrode active material C2 (Li 0.48 Mn 0.50 Ni 0.20 Co 0.30 O2) is used.

[0192] [Manufacturing of Solid-State Batteries]

[0193] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material C2 for a lithium-ion battery.

[0194] <Comparative Example 3>

[0195] [Manufacture of positive electrode active material for lithium-ion batteries]

[0196] In the (Na-doped precursor synthesis process), regarding the intermediate powder, Na2CO3, Na 0.65 Mn 0.5 Ni 0.2 Co 0.3 A positive electrode active material for a lithium-ion battery was obtained in the same order as in Example 1, except that O2 was added. The positive electrode active material for a lithium-ion battery is lithium-ion battery positive electrode active material C3 (Li 0.62 Mn 0.50 Ni 0.20 Co 0.30 It is done as O2).

[0197] [Manufacturing of Solid-State Batteries]

[0198] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material C3 for a lithium-ion battery.

[0199] <Comparative Example 4>

[0200] [Manufacture of positive electrode active material for lithium-ion batteries]

[0201] Lithium carbonate (Li2CO3), manganese oxide (MnO2), nickel oxide (NiO), and cobalt oxide (Co2O3) were mixed in a ball mill. Pellet was produced by pressing with a load of 2 ton using a cold isostatic pressing method. The obtained pellets were calcined in air at 1000 °C for 24 hours to produce the positive electrode active material C4 (Li2CO3) for lithium-ion batteries. 1.0 Mn 0.33 Ni 0.33 Co 0.33 Obtained O2.

[0202] [Manufacturing of Solid-State Batteries]

[0203] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material C4 for a lithium-ion battery.

[0204] <Comparative Example 5>

[0205] [Manufacture of positive electrode active material for lithium-ion batteries]

[0206] Lithium nitrate (LiNO3) was used as the positive electrode active material C5 for lithium-ion batteries.

[0207] [Manufacturing of Solid-State Batteries]

[0208] (Preparation process) -Preparation of the positive electrode layer-, a coin cell battery was manufactured in the same order as in Example 1, except that the positive electrode active material 1 for a lithium-ion battery was changed to the positive electrode active material C5 for a lithium-ion battery.

[0209] <Evaluation>

[0210] (Peak location and space group in X-ray diffraction measurement results)

[0211] Table 1 shows the results calculated according to the previously described order for the “number of peaks in the range where 2θ is 64° or more and 70° or less,” the “number of peaks in the range where 2θ is 15° or more and 20° or less,” and the “space group” of the positive electrode active material for lithium-ion batteries included in the batteries obtained in each example.

[0212] (Initial discharge capacity)

[0213] A charge-discharge test was conducted using a galvanostat under conditions of a current of 0.1 C, a charge termination voltage of 4.8 V, and a discharge termination voltage of 2.0 V. Charging was started, and after the first charge was completed, the amount of current required to discharge to 2.0 V was calculated, and the initial discharge capacity was calculated by dividing by the weight of the active material used for measurement.

[0214] (Capacity retention rate after 20 cycles)

[0215] A charge-discharge test was performed under the same conditions as above, and the discharge capacity of the 1st and 20th cycles was calculated. The discharge capacity of the 20th cycle was divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate after 20 cycles.

[0216]

[0217] In Table 1, “number of peaks at 2θ = 64° to 70°” refers to the number of peaks that exist in the range where 2θ is 64° or more and 70° or less.

[0218] In Table 1, “number of peaks at 2θ = 15° to 20°” refers to the number of peaks that exist in the range of 2θ being 15° or more and 20° or less.

[0219] From the above results, it can be seen that the positive electrode active material for a lithium-ion battery of the present embodiment yields a battery with a high initial discharge capacity and a high capacity retention rate after repeated charging and discharging. Explanation of the symbols

[0220] A : Pole layer B: Solid electrolyte layer C : Positive polar layer 101 : Negative electrode active material 102 : Solid electrolyte 103 : Positive electrode active material 105 : Challenge Supplement 109, 111 : Binder 113 : Bu-geuk entire house 115 : Entire house of a straight play

Claims

Claim 1 A positive electrode active material for a lithium-ion battery, wherein, in the X-ray diffraction measurement results, there are three or more peaks in the range of 2θ from 64° to 70° and one peak in the range of 2θ from 15° to 20°, is attributed to the space group Cmca, comprises Li, Ni, Co, and Mn, and is a compound represented by the following Formula 1. Formula 1: Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2(wherein in Equation 1 above, a, b, x, y, z, p, q, and r are numbers satisfying 0 < a ≤ 1, 0 ≤ b ≤ 0.05, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and M represents at least one type selected from the group consisting of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.) Claim 2 delete Claim 3 delete Claim 4 A positive electrode material comprising a positive electrode active material for a lithium-ion battery as described in claim 1. Claim 5 A solid-state battery comprising a positive electrode active material for a lithium-ion battery as described in claim 1. Claim 6 A method for manufacturing a positive electrode active material for a lithium-ion battery according to claim 1, comprising a process of ion-exchanging Na contained in a compound represented by Formula 2 below with Li. Formula 2: Na c Mn x-p Ni y-q Co z-r M p+q+r O2(wherein in Equation 2 above, c, x, y, z, p, q, and r are numbers satisfying 0.5 ≤ c ≤ 0.65, x + y + z = 1, and 0 ≤ p + q + r ≤ 0.20, and M represents at least one type selected from the group consisting of Li, B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, Mo, and W.)

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery and manufacturing method of cathode

    JP2009032681A